2011
DOI: 10.1016/j.powtec.2010.10.020
|View full text |Cite
|
Sign up to set email alerts
|

On the minimum fluidization velocity in 2D fluidized beds

Abstract: a b s t r a c tIn the present study, a new correlation for the determination of the minimum fluidization velocity in 2D fluidized beds was developed. The proposed correlation was based on the experimental results obtained in 2D fluidized beds with different particle sizes, bed thicknesses and bed heights. Thus, the proposed correlation depends only on the nondimensional variable t/d p , where t is the bed thickness and d p is the particle size. The proposed correlation was compared with other experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 41 publications
(76 reference statements)
4
21
1
Order By: Relevance
“…Sánchez Delgado et al (2011) established that U mf increases when decreasing the bed thickness below a certain critical thickness. Above this critical thickness the wall effect is negligible and the behavior is like a 3D bed.…”
Section: Methodsmentioning
confidence: 99%
“…Sánchez Delgado et al (2011) established that U mf increases when decreasing the bed thickness below a certain critical thickness. Above this critical thickness the wall effect is negligible and the behavior is like a 3D bed.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we decided to investigate how the choice of bed depth value affects the numerical prediction of In the literature, the effect of the bed thickness has mainly been studied with respect to the minimum fluidization velocity. It was observed that the latter increases as the bed thickness decreases (Caicedo et al, 2002;Kathuria & Saxena, 1987;Sanchez-Delgado et al, 2011;Saxena & Vadivel, 1988). This is because, as the bed depth reduces, the effect of wall friction becomes more pronounced, limiting the movement of the particles.…”
Section: Dem Simulationsmentioning
confidence: 98%
“…Because of the viscosity of the quasi-liquid (fluidized bed), the moving medium in upper layer would drive the lower layer medium to move in the same directionat a lower speed. Due to the back-mixing of the dense medium powders in ADMFB (Luo et al, 1996;Luo et al, 2008), the merge and breakage of the bubbles are quite complicated in the practical experimental operation (Hernández-Jiménez et al, 2013;Sánchez-Delgado et al, 2011;Zou et al, 2011). As a result, the actual distribution of the bed velocity varies and becomes complicated.…”
Section: Effect Of Scraper Movement On the Bed Densitymentioning
confidence: 99%